A comparative assessment of micro drilling in boron carbide using ultrasonic machining. Issue 1 (2nd January 2020) - Haashir, Ahmad; Debnath, Tapas; Patowari, Promod Kumar
ABSTRACT: In the present work, machining of boron carbide (B4 C) has been performed using ultrasonic machining (USM) with the same material as abrasive particles. A comparative assessment of machining of B4 C with that of glass and brass has also been carried out by drilling microholes using USM. The experimentation has been conducted according to Taguchi L9 orthogonal array. The effect of feed rate, slurry concentration, and grit size has been evaluated on the performance measures such as material removal rate, overcut, circularity error, taper angle and tool wear rate. Additionally, overall evaluation criteria (OEC) has been formulated to evaluate the combined performance measures. After ANOVA feed rate became the most significant parameters affecting OEC for all the materials. The machining of B4 C has been found to be possible but lacks in the machining rate in comparison with that of glass and brass. Least tool wear rate has been found in case of glass whereas minimum overcut, circularity error and taper angle have been observed for brass. The quality of the drilled holes in B4 C is better as minimal surface chipping and burr formation has been observed.